Intrathecal/Intraventricular Linezolid in Multidrug-Resistant Enterococcus faecalis Ventriculitis - Lich, Brian F.; Conner, Andrew K.; Burks, Joshua D.; Glenn, Chad A.; Sughrue, Michael E. (Journal of Neurological Surgery Reports, 2016)
Background The use of intrathecal antibiotic therapy for the treatment of ventriculitis and/or meningitis has demonstrated efficacy especially when sterilization of the cerebrospinal fluid is not possible with intravenous antibiotics alone.Case Description We describe the successful treatment of Enterococcus faecalis ventriculitis utilizing intrathecal linezolid in a 32-year-old female patient with severe allergy to vancomycin, prohibitive bacterial susceptibilities, and failure of previous attempts to sterilize the cerebrospinal fluid despite multimodal treatment.Conclusion Intrathecal linezolid is a useful treatment in the setting of multidrug-resistant bacterial ventriculitis. We present a useful dosing regimen for the administration of intrathecal linezolid.
Keywords: intrathecal; ventriculitis; linezolid; external ventricular drain